International Trade and Unemployment: A Quantitative Framework - Benedikt Heid; Mario Larch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Quantifying the welfare effects of trade liberalization is a core issue in international trade. Existing frameworks assume perfect labor markets and therefore ignore the effects of aggregate employment changes for welfare. We develop a quantitative trade framework which explicitly models labor market frictions. To illustrate, we assess the effects of trade and labor market reforms for 28 OECD countries. Welfare effects of trade agreements are magnified when accounting for employment changes. While employment and welfare increase in most countries, some experience higher unemployment and lower welfare. Labor market reforms in one country have small positive spillover effects on trading partners.
Keywords: F16; F13; F14; 330